The Effect of Income Tax, Leverage and Exchange Rate on Transfer Pricing (Study on Manufacturing Industry 2016-2020) - Puspa Rini; M. Reza Oktananda (PT. Altaf Publishing Corp, 2025)
This study aims to examine the effect of income tax, leverage, and exchange rate variables on transfer pricing. This study took samples of manufacturing companies listed on the Indonesia Stock Exchange, especially the various industrial sectors from 2016-2020. In this study, the sample used was 16 company samples selected using the purposive sampling method. The analysis technique used in this study used Multiple Linear Regression analysis. The research data used financial reports accessed through the official website of the Indonesia Stock Exchange (IDX). The results of this study indicate that income tax, leverage and exchange rate have a significant positive effect on transfer pricing.